Japan's Education Services Imports: Branch Campus or Subsidiary Campus? - Shintaro Hamanaka (Asian Development Bank (ADB), 2012)
On the one hand, trade in tertiary education is highly regulated; on the other hand, it is a considerably liberalized area of services. This is especially true in the case of Mode 3 of international services trade, namely oversea campuses. In the case of Japan, foreign universities are/were free to open campuses in Japan to supply tertiary education services, but those were regarded informal education that was not recognized by the Japanese government until 2004. For campuses in Japan established by foreign universities to supply formal education services in Japan, they are required to satisfy the criteria set by the government to be examined by the University Council and the Minister; but no foreign university campus in Japan actually obtained a formal school status. Moreover, program at the campuses in Japan were not regarded as an equivalent to the program provided at the home campuses abroad. It was only in 2004 when the Japanese government introduced a new scheme called "Japanese Branches of Foreign Universities", under which they can receive the treatment similar to formal Japanese universities except taxation, though only four campuses obtained this status so far. This paper reviews the development of regulatory status of services trade in tertiary education services, especially education through oversea campuses, and considers the policy implications on two critical issues regarding the regulation of services industry: (i) who between the government and the University Council the regulator is; and (ii) who between the home country and host country has the jurisdiction over the oversea branches of universities.
hdl:11540/1255
Keywords: F19; L80; L88; 330; Trade in services; education services; overseas campus; regulations; banking; Hochschule; Dienstleistungshandel; Regulierung; Japan